Analysis on the implementation of mindfulness practice in education to support teaching and learning’s progress - Hosea, Eveline (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
The purpose of this research is to describe the impacts of mindfulness practice in education and the progress of teaching and learning. It also describes the impacts of mindfulness practice on the progress of teaching and learning. This research is done by using qualitative analysis descriptive method with literature study. There are a few steps in describing the data by collecting the research articles, books, journals and other types of literature that are related to the impacts of mindfulness practice. The result of this research is that mindfulness practice will help in many ways that can increase the teacher and students capacity while teaching and learning, such as improving concentration, resilience to stress, writing competency, communication skills and the motivation to study.